Arterio-ureteral fistula: A case-based review of significant hematuria - Roberto Cunha; Manuel Silva; Pedro Sousa; Mafalda Correia; Isabel Vieira; Isabel Cássio; Nelson Oliveira; Emanuel Dias (Angiologia e Cirurgia Vascular)
BACKGROUND: Arterio-ureteral fistula (AUF) is a rare but life-threatening cause of hematuria. Most AUFs are secondary to malignancy or extensive pelvic/ vascular surgery